Deep subsurface sulfate reduction and methanogenesis in the Iberian Pyrite Belt revealed through geochemistry and molecular biomarkers. Issue 1 (16th November 2013) - Puente‐Sánchez, F.; Moreno‐Paz, M.; Rivas, L. A.; Cruz‐Gil, P.; García‐Villadangos, M.; Gómez, M. J.; Postigo, M.; Garrido, P.; González‐Toril, E.; Briones, C.; Fernández‐Remolar, D.; Stoker, C.; et al.
Abstract The Iberian Pyrite Belt (IPB, southwest of Spain), the largest known massive sulfide deposit, fuels a rich chemolithotrophic microbial community in the Río Tinto area. However, the geomicrobiology of its deep subsurface is still unexplored. Herein, we report on the geochemistry and prokaryotic diversity in the subsurface (down to a depth of 166 m) of the Iberian Pyritic belt using an array of geochemical and complementary molecular ecology techniques. Using an antibody microarray, we detected polymeric biomarkers (lipoteichoic acids and peptidoglycan) from Gram‐positive bacteria throughout the borehole. DNA microarray hybridization confirmed the presence of members of methane oxidizers, sulfate‐reducers, metal and sulfur oxidizers, and methanogenic Euryarchaeota. DNA sequences from denitrifying and hydrogenotrophic bacteria were also identified. FISH hybridization revealed live bacterial clusters associated with microniches on mineral surfaces. These results, together with measures of the geochemical parameters in the borehole, allowed us to create a preliminary scheme of the biogeochemical processes that could be operating in the deep subsurface of the Iberian Pyrite Belt, including microbial metabolisms such as sulfate reduction, methanogenesis and anaerobic methane oxidation.